Chemical characterization and biological activity of Chaga (Inonotus obliquus), a medicinal “mushroom” - Glamočlija, Jasmina (2015)
Chemical composition and biological properties of aqueous and ethanolic extracts of Inonotus obliquus (Pers.:Fr.) Pilat from different origins, i.e. of Finland, Russia, and Thailand, were studied. Concerning biological activity, antimicrobial, antiqourum, antioxidative, and antitumor and cytotoxic effects were tested. Oxalic acid was found as the main organic acid, with the highest amount in Russian aqueous extract. Gallic, protocatechuic and p-hydroxybenzoic acids were detected in all samples. I. obliquus extracts showed high antioxidant and antimicrobial activity. Extracts were tested at subMIC for anti-quorum sensing (AQS) activity in Pseudomonas aeruginosa and all of them showed definite AQS activity. The assays were done using twitching and swarming of bacterial cultures, as well as the amount of produced pyocyanin as QS parameters. All the extracts possessed good antitumor effect on four cells lines and did not show hepatotoxicity on porcine liver primary cells designed as PLP2. As the I. obliquus presence in Chaga conks is limited, further purification is necessary to draw quantitative conclusions. The presence of AQS activity in medicinal mushrooms suggests a broader anti-infectious disease protection than only immunomodulatory effects.